Safety First and Hedging - Telser, Lester G. (Review of Economic Studies, 1955)
Journal Article Safety First and Hedging Get access Lester G. Telser Lester G. Telser Chicago Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 23, Issue 1, 1955, Pages 1–16, https://doi.org/10.2307/2296146 Published: 01 April 1955